Quality of the Selection of Patients with Respiratory Symptoms According to the Risk of Pulmonary Tuberculosis - Yuri Arnold Domínguez (Medisur)
Background: the program for the detection of pulmonary tuberculosis is based on cases detection by passive and active searching. The latter focuses on patients with respiratory symptoms spontaneously visiting medical consultation, which is very important to know to select patients at risk for tuberculosis. Objective: To assess the quality of the selection of patients with respiratory symptoms according to the risk of pulmonary tuberculosis. Methods: A retrospective and descriptive study was conducted between September 2004 and September 2005 including patients with respiratory symptoms of 14 days and more of evolution, belonging to the health area of the Antonio Guiteras polyclinic in the municipality of Old Havana. The following variables were analyzed: age, risk factors, sample quality, culture quality and performance of the health team in monitoring patients with respiratory symptoms. Results: The average age was 20.0 ± 61.0 years old. Out of the surveyed patients with respiratory symptoms, retirees accounted for 45.8%. All sputum samples were helpful samples, 12.5% of the cultures were not performed because of contamination or inadequate samples. 12.5% of patients needed more follow-up after diagnosis and 18.8% did not improve. 81% of the patients presented at least one risk factor. Conclusions: the importance of surveys in order to monitor patients with respiratory symptoms according to the risks of tuberculosis becomes paramount with this study.